Users' and Librarians' Perceptions of School Resource Center KOHA Library Automation Implementation: A Case Study of School Resource Centre at Kolej Tingkatan Enam Petaling Jaya. - Wahidah, Mohd Zain; Amir Hussain, Md Ishak; Norkamarizal, Kamarudin; Aida Rashidah, Maajis; Nur Liyana, Abdul Halil (2019)
This paper discusses the findings of qualitative and quantitative data analysis on users’ and librarians’ perceptions of school resource center KOHA library automation which has been installed in the library. Descriptive statistics by using SPSS analysis tool shows that the use of KOHA at the school resource centre has resulted in positive feedback from the users. The respondents perceived themselves moderately high for all statements on reliability, personalized search, information security, flexibility, functional benefit and benefit in supporting teaching and learning process. The installation of KOHA is part of an outreach program for the community, by Asia e University Knowledge Centre. The initiative is aligned with the Digital Malaysia program, which was designed to promote the use of ICT which can improve the livelihood of society and education. Furthermore, librarians may help in supporting the education system and upholding a quality education system in general by working together with other librarians regardless of the difference in terms of the library type.